Lenticel hydration alters the susceptibility of apple fruit to infection by Phlyctema vagabunda - Everett, Kerry R.; Hasna, Luna; Pushparajah, Irene P. S.; Vergara, Michelle J.; Wood, Peter N.; Fisher, Brent M.; Sutherland, Paul S.; Richards, Kate K.; Husheer, Sean W. (Frontiers in Horticulture, 2023)
Bull’s eye rot, caused by Phlyctema vagabunda, is an important postharvest rot of apples. A combination of laboratory and field trials were conducted to examine the relationship between infection and status of apple lenticels. Fruit were hydrated and then inoculated, and climatic factors were compared with inoculations and natural infections in the field. In laboratory trials it was shown that increased lenticel density and size led to more infections. Hydration distended lenticel diameter, and dehydration contracted lenticels. A strong relationship with wind run, leaf wetness and temperature were shown to be important for laboratory inoculations of monthly harvested fruit, natural infections in trap fruit experiments, and monthly field inoculations. It was hypothesised that high wind run (> c. 240 km/day) reduced fruit susceptibility by promoting lenticel closure, and when lenticels were open, temperature limited the formation of an infection stroma. If the stroma did not form, postharvest expression of disease was negligible. Leaf wetness over 28 days was also an important factor for infection, probably because of the effect on micro-crack formation and resealing of lenticels during maturation by components of the cuticle. From these results, pre-harvest application of compounds that close lenticels could provide some control of bull’s eye rot without the need for fungicides.